Male genital lichen sclerosus - Christopher Barry Bunker; Tang Ngee Shim (Wolters Kluwer Medknow Publications, 2015)
Male genital lichen sclerosus (MGLSc) is a chronic inflammatory skin disease responsible for male sexual dyspareunia and urological morbidity. An afeared complication is squamous cell carcinoma (SCC) of the penis. The precise etiopathogenesis of MGLSc remains controversial although genetic, autoimmune and infective (such as human papillomavirus (HPV) hepatitis C (HCV), Epstein-Barr virus (EBV) and Borrelia) factors have been implicated: Consideration of all the evidence suggests that chronic exposure of susceptible epithelium to urinary occlusion by the foreskin seems the most likely pathomechanism. The mainstay of treatment is topical ultrapotent corticosteroid therapy. Surgery is indicated for cases unresponsive to topical corticosteroid therapy, phimosis, meatal stenosis, urethral stricture, carcinoma in situ (CIS) and squamous cell carcinoma.